A Two-Dimensional Non-Relativistic Quantum Physics Game Engine - Vargas, Luan P.; Thielo, Marcelo R.; Martins-Filho, Luiz S.; Brandt, Ueslei (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This paper presents an engine for creating interactive games using concepts from quantum mechanics, aiming to provide users with a tool capable of assisting in the creation of playable experiences that may help consolidate basic concepts in the field. We implemented a quantum simulation library based on the Schrödinger equation using the relaxation method. The prototype has a range of functions that already allow the creation of an interactive interface, in addition to quantum simulation capabilities. As a result, a prototype of a simple game was developed to demonstrate the current functionalities of the engine.